Caracterización de las pandillas salvadoreñas a través de la crónica periodística (2022)
The Mara Salvatrucha 13 and Barrio 18 gangs are the protagonists of recent journalistic chronicles in El Salvador. Through the qualitative analysis of a corpus of chronicles on the gang phenomenon during the governments of the Farabundo Martí National Liberation Front (Frente Farabundo Martí para la Liberación Nacional, FMLN), information contained in the journalistic narrative on four fundamental topics is recovered: 1) the genesis and expansion of gangs; 2) the characterization of gangs by investigative journalism, with an emphasis on the phenomena of territorial control; 3) the narrative about gang violence through emblematic characters; and 4) the contrast between negotiation and confrontation that characterized the FMLN governments in dealing with the gangs problem.